A study of low velocities regions near the Roche lobe during the gas giant planets formation - Moraes, Ricardo A. [UNESP]; Vieira Neto, Ernesto [UNESP]; IOP (Iop Publishing Ltd, 2013)
In this paper were studied regions close to the Roche lobe of a planet like Jupiter, in order to find regions with low velocities. We simulated a two dimensional and non-self-gravitating disk, where tidal and viscous torques are considered, using the hydrodynamic numerical integrator FARGO 2D. As stated earlier we are interested in find low velocities regions for in future works study the possibility of satellites formation in these regions.